A clinico-etiological evaluation and EEG correlation of neonatal seizures in a tertiary care hospital: a prospective cohort study - Sharma, Kuldeep Kumar; Paimode, Sandeep D.; Kour, Navjot (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal seizure is defined as a paroxysmal alteration in neurological function. The diagnosis of neonatal seizures is difficult to establish because of varied etiologies involved. The incidences vary from 1.5-3.7/1000 live births in term babies. Methods: Hospital based observational study was conducted from December 1, 2016 till March 31, 2018. Universal sampling technique was followed. 93 neonates fulfilling the inclusion criteria were included in the study after consent from parents. Results: This study results showed that 60.2% were males. Pre-term delivery occurred in 12.9% neonates. Most common etiology of neonatal seizures was birth asphyxia with 47.3% followed by metabolic abnormalities 32.3%. Abnormal EEG pattern was seen in 29% cases of neonatal seizures. Conclusions: To conclude, the most common aetiology for neonatal seizures was birth asphyxia followed by metabolic abnormalities in which hypoglycaemia was the most common type. A significant association of seizures due to meningitis and metabolic abnormalities was observed with pre-term gestation while abnormal EEG pattern was observed with birth asphyxia and meningitis. EEG findings were found normal in majority of cases of neonatal seizure.